PROJECT PLANNING OF VIADUCT STRUCTURE IN LRT JAKARTA PHASE 1B ZONE 1 - Fiorenza Melati Putri Diangga; Fauzi Akbar Rahmawan (Jurnal Online Skripsi Manajemen Rekayasa Konstruksi (JOS-MRK), 2025)
The LRT Jakarta Phase 1B Zone 1 Velodrome – Manggarai construction project is a project owned by PT. Jakarta Propertindo (PERSERODA) which is located on East Jakarta, District Pulo Gadung and Matraman. This project consists of 103 piers with a length of 3,6 km. This project will be implemented in the middle of a densely populated road surrounded by high-rise buildings, schools, and a university with limited construction area. So that we need project planning for this project to determine the appropriate organizational structure, site layout, implementation method, quality and safety planning, implementation budget, implementation time. To create project planning there are some required data, such as shop drawing, work plan document and requirements, and DKI Jakarta unit price document 2023. The result of project planning that have been prepared are the organizational structure used is a functional type of organization, site layout consist of 10 temporary facilities the planning of which is divided into 2 alternatives and traffic management has 2 access doors, namely entrance and exit for each section, the implementation strategy uses zoning, Quality planning consists of Standard Operational Procedure (SOP), and For safety planning consists of K3L, organizational structure, Hazard Identification Risk Assessment and Risk Control (HIRARC), General Program, and K3 Supporting Equipment, Implementation Time 843 Calendar Days with a total implementation budget of Rp. 453.955.638.849,71.